Simulations of VLBI observations with the Onsala Twin Telescope - Schönberger, Caroline (My University, 2013)
The VLBI 2010 committee of the International VLBI Service for Geodesy and Astrometry (IVS) developed a concept to achieve an improvement of the accuracy of geodetic Very Long Baseline Interferometry (VLBI) to 1 mm for station position and 0.1 mm/yr for station velocity. This so-called VLBI2010 concept includes broad-band observations with fast slewing telescopes and proposes twin telescopes to improve the handling of atmospheric turbulence that has been identified as a limited factor for geodetic VLBI. Several international projects following the VLBI2010 concept have been started in the last years. One of them is the Onsala Twin Telescope project which is expected to start operating in 2016. In this study a global VLBI network is scheduled, simulated and analysed. The chosen network is the CONT11 network, a 15 days long continuous VLBI campaign performed in 2011 that gave the current state-of-the-art geodetic VLBI results. Results derived from simulated observations in this network including either the legacy 20 m radio telescope at Onsala or the planned Onsala Twin Telescope are compared. The comparisons include station positions, earth orientation parameter, atmospheric parameter and clock estimations. A general improvement can be noted with the Onsala twin telescope. The best results are derived with the twin telescope operating in continuous mode.
Keywords: Grundläggande vetenskaper; Geovetenskap och miljövetenskap; Basic Sciences; Earth and Related Environmental Sciences